THE IMPACT OF CARBON REGULATION MECHANISMS ON THE DEVELOPMENT OF INDUSTRY IN THE RUSSIAN FEDERATION - M. M. Balashov (Стратегические решения и риск-менеджмент, 2021)
The European Commission is currently preparing to implement a new form of carbon regulation a cross-border carbon tax. As conceived by the authors, such a decision will force exporters of goods with a significant amount of greenhouse gas emissions during production to improve the environmental friendliness of production and, as a result, to reduce their carbon footprint. In addition, the carbon tax will create a competitive advantage for foreign companies with low greenhouse gas emissions. Such a policy of the European Union can seriously affect the economy of the Russian Federation and Russian companies that are export-oriented. Today, all over the world, more and more importance is attached to environmentally neutral technologies and industries. To keep up with the global trend, as well as to maintain the level of competitiveness, the Russian economy needs to adapt. The speed and efficiency of adaptation directly depend on system solutions both at the state level (development of the necessary regulatory legal acts and standards for reporting and disclosure of information) and at the level of enterprises most sensitive to carbon regulation (audit of the carbon footprint, modernization of production facilities, responsible approach to neutralization carbon footprint). The purpose of this work is to study the impact of carbon regulation mechanisms on the development of industry in the Russian Federation, in accordance with it, the following tasks are formed: to describe the mechanisms of carbon regulation, to assess the economic impact on the domestic industry, to consider world practices of confirming the carbon footprint, to identify threats to implementation of the national program “International cooperation and export” from the introduction of carbon regulation.